Pleiotrophin and metabolic disorders: insights into its role in metabolism - Ballesteros-Pla, Cristina; Sánchez-Alonso, María Gracia; Pizarro-Delgado, Javier; Zuccaro, Agata; Sevillano, Julio; Ramos-Álvarez, María Pilar (Frontiers in Endocrinology, 2023)
Pleiotrophin (PTN) is a cytokine which has been for long studied at the level of the central nervous system, however few studies focus on its role in the peripheral organs. The main aim of this review is to summarize the state of the art of what is known up to date about pleiotrophin and its implications in the main metabolic organs. In summary, pleiotrophin promotes the proliferation of preadipocytes, pancreatic β cells, as well as cells during the mammary gland development. Moreover, this cytokine is important for the structural integrity of the liver and the neuromuscular junction in the skeletal muscle. From a metabolic point of view, pleiotrophin plays a key role in the maintenance of glucose and lipid as well as whole-body insulin homeostasis and favors oxidative metabolism in the skeletal muscle. All in all, this review proposes pleiotrophin as a druggable target to prevent from the development of insulin-resistance-related pathologies.